2005
DOI: 10.1021/bi050401x
|View full text |Cite|
|
Sign up to set email alerts
|

Structural Basis for Antagonism by Suramin of Heparin Binding to Vaccinia Complement Protein,

Abstract: Suramin is a competitive inhibitor of heparin binding to many proteins, including viral envelope proteins, protein tyrosine phosphatases, and fibroblast growth factors (FGFs). It has been clinically evaluated as a potential therapeutic in treatment of cancers caused by unregulated angiogenesis, triggered by FGFs. Although it has shown clinical promise in treatment of several cancers, suramin has many undesirable side effects. There is currently no experimental structure that reveals the molecular interactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…We examined the effect of complexes 1 , 2 , and 3 with or without VEGF on the HUVECs’ migration, as measured by the wound healing assay. Suramin exhibits its antitumor activity in various cell lines [30, 31], which has been clinically evaluated as a potential therapeutic in treatment of cancers caused by VEGF-induced angiogenesis; therefore, we have chosen it as a positive control. Figure 5(a) showed that for VEGF-induced angiogenesis, VEGF facilitated repair of the wounded monolayer by 24 h, and a significant area of the wound remained uncovered when treated with complexes 1 , 2 , and 3 compared to the control.…”
Section: Resultsmentioning
confidence: 99%
“…We examined the effect of complexes 1 , 2 , and 3 with or without VEGF on the HUVECs’ migration, as measured by the wound healing assay. Suramin exhibits its antitumor activity in various cell lines [30, 31], which has been clinically evaluated as a potential therapeutic in treatment of cancers caused by VEGF-induced angiogenesis; therefore, we have chosen it as a positive control. Figure 5(a) showed that for VEGF-induced angiogenesis, VEGF facilitated repair of the wounded monolayer by 24 h, and a significant area of the wound remained uncovered when treated with complexes 1 , 2 , and 3 compared to the control.…”
Section: Resultsmentioning
confidence: 99%
“…When infection was performed in 2% serum with the addition of suramin (Fig. 3B), a molecule that binds and inhibits the activity of many of the heparinbinding growth factors (Moscatelli and Quarto, 1989;Ganesh et al, 2005), the heparin enhancement was abrogated, reinforcing the need for the presence of growth factors to achieve the heparin augmentation effect.…”
Section: Fig 1 Aav1 Aav2 and Aav3b Exhibit Different Transductionmentioning
confidence: 97%
“…Low to moderate levels of GF (which may more closely reflect an in vivo scenario) are essential, not detrimental, to the enhancement. Removing them from the infection either through performing the infections under serum-free conditions, or by using suramin (a drug that blocks the biological activity of heparin-binding growth factors) (Moscatelli and Quarto, 1989;Ganesh et al, 2005), abolishes the affect. Addition of the growth factor back to the cells reconstitutes this effect.…”
Section: Aav3b Vector Transduction By Fgfr Systemmentioning
confidence: 99%
“…Previously [7,16], the specific complexing behavior of alkali metal or alkaline earth metal ions with p-toluenesulfonate and 1,5-naphthalenedisulfonate ions has been thoroughly investigated in MeCN, alcohols, and binary solvents of MeCN-H 2 O and MeCN-alcohols. Naphthalenetrisulfonate is commonly used as a chemical function of Suramin and Suradistas [28].…”
Section: Introductionmentioning
confidence: 99%